Mississippi Entrepreneurs - Dement, Polly (Book collections on Project MUSE., 2014)
"The stories in Mississippi Entrepreneurs draw attention to the tenacious and courageous journeys of Mississippi men and women who risk fortune and futures to create successful enterprises. Most tell "how they did it" uniquely and in their own words; family members and former colleagues pick up the storyline for legendary entrepreneurs who have passed on, recalling vividly the characteristics that set them apart from the competition. Usually a passion for creation inspired these go-getters--whether casting liquid steel into industrial products (Fred Wile, Meridian); constructing buildings (Roy Anderson III, Gulfport; Bill Yates Jr., Philadelphia); making agricultural products grow (Janice and Allen Eubanks, Lucedale; Mike Sanders, Cleveland); delivering and installing furniture (Johnnie Terry, Jackson); using technology to improve systems (John Palmer and Joel Bomgar, Jackson; Billy and Linda Howard, Laurel); expanding food operations (S.L. Sethi, Jackson; Don Newcomb, Oxford); or sharing the sheer love of music (Hartley Peavey, Meridian), food (Robert St. John, Hattiesburg), art (Erin Hayne and Nuno Gonsalves Ferreira, Jackson), or books (John Evans, Jackson; Richard Howarth, Oxford). Social and cultural entrepreneurs made their marks as well, including those focused on social justice (Martha Bergmark, Jackson); access to health care (Aaron Shirley, Jackson); and public education (Jack Reed, Tupelo). Few if any books have focused exclusively on this aspect of the state's history. Altogether these stories illustrate common traits, including plentiful vision, fierce drive, willingness to take risks and change for a better way, the ability to innovate, solve problems, and turn luck to advantage"--